2021
DOI: 10.3390/rs13224507
|View full text |Cite
|
Sign up to set email alerts
|

Global Fisheries Responses to Culture, Policy and COVID-19 from 2017 to 2020

Abstract: Global Fishing Watch (GFW) provides global open-source data collected via automated monitoring of vessels to help with sustainable management of fisheries. Limited previous global fishing effort analyses, based on Automatic Identification System (AIS) data (2017–2020), suggest economic and environmental factors have less influence on fisheries than cultural and political events, such as holidays and closures, respectively. As such, restrictions from COVID-19 during 2020 provided an unprecedented opportunity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
(48 reference statements)
3
6
0
Order By: Relevance
“…Fishing pressure inevitably declined during the Covid‐19 lockdown (Kemp et al, 2020), whereas harvest remained high for many member states (STECF, 2021, 2022). Results of the present study showed that harvest and economic inefficiency increased for many European Union member states, similar to fisheries elsewhere in the world (He et al, 2021). Before the outbreak (2017–2019) and followed by 2020, when lockdowns for the outbreak began, fishing efforts increased and concentrated in European Union territorial waters, similar to areas of the Pacific Ocean and Chinese high seas, with an apparent dominance by trawlers and long‐liners (He et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Fishing pressure inevitably declined during the Covid‐19 lockdown (Kemp et al, 2020), whereas harvest remained high for many member states (STECF, 2021, 2022). Results of the present study showed that harvest and economic inefficiency increased for many European Union member states, similar to fisheries elsewhere in the world (He et al, 2021). Before the outbreak (2017–2019) and followed by 2020, when lockdowns for the outbreak began, fishing efforts increased and concentrated in European Union territorial waters, similar to areas of the Pacific Ocean and Chinese high seas, with an apparent dominance by trawlers and long‐liners (He et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…Results of the present study showed that harvest and economic inefficiency increased for many European Union member states, similar to fisheries elsewhere in the world (He et al, 2021). Before the outbreak (2017–2019) and followed by 2020, when lockdowns for the outbreak began, fishing efforts increased and concentrated in European Union territorial waters, similar to areas of the Pacific Ocean and Chinese high seas, with an apparent dominance by trawlers and long‐liners (He et al, 2021). The European Union financial aid during the Covid‐19 lockdown decreased vulnerability and increased resilience of the European Union fisheries (Le Brenne et al, 2021) in addition to stable harvest.…”
Section: Discussionsupporting
confidence: 73%
“… ‘Fishing gears’ ordered by classification in (He et al, 2021). ‘Auxiliary devices’ and ‘Other fishing practices’ ordered alphabetically.…”
Section: Resultsmentioning
confidence: 99%
“…‘trash fishing’). Where references to practices were sufficiently detailed in the reference to specific gears and/or auxiliary devices, we used the classification system in He et al (2021), which is an objective, multi‐lingual lexicon of fishing technology developed by FAO gear technologists. From our records, we identified 40 separate fishing practices associated with the term ‘destructive fishing’ across the three content types; 24 identifiable fishing gears, five auxiliary fishing devices and 11 other fishing practices/fishing‐associated behaviours.…”
Section: Methodsmentioning
confidence: 99%
“…“trash fishing”). Where references to practices were sufficiently detailed in the reference to specific gears and/or auxiliary devices, we used the classification system in (He et al, 2021), which is an objective, multi-lingual lexicon of fishing technology developed by FAO gear technologists. From our records, we identified 40 separate fishing practices associated with the term “destructive fishing” across the three content types; 24 identifiable fishing gears, five auxiliary fishing devices and 11 other fishing practices/fishing associated behaviours.…”
Section: Methodsmentioning
confidence: 99%